2014
DOI: 10.1186/1756-0500-7-860
|View full text |Cite
|
Sign up to set email alerts
|

Testing the sexual imagination hypothesis for gender differences in response to infidelity

Abstract: BackgroundEvolutionary psychologists hypothesized that men are more upset by sexual infidelity than women are, whereas women are more upset by emotional infidelity than men are. On the other hand, the sexual imagination hypothesis states that gender differences in infidelity responses are derived from explicit men’s sexual imagery. Based on the latter hypothesis, we hypothesized that although men would report being more distressed by sexual infidelity than women who were not in a committed relationship (NCR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
(39 reference statements)
4
16
0
1
Order By: Relevance
“…As the conclusions in the previous study suggested, the findings on relationship status indirectly supported the imagination hypothesis on infidelity responses because no significant gender differences in jealousy were found for a sample of individuals who were in committed relationships (e.g. Guadagno & Sagarin, 2010;Kato, 2014aKato, , 2014bVoracek, 2001). However, a few studies (e.g.…”
Section: Relationship Statussupporting
confidence: 66%
See 4 more Smart Citations
“…As the conclusions in the previous study suggested, the findings on relationship status indirectly supported the imagination hypothesis on infidelity responses because no significant gender differences in jealousy were found for a sample of individuals who were in committed relationships (e.g. Guadagno & Sagarin, 2010;Kato, 2014aKato, , 2014bVoracek, 2001). However, a few studies (e.g.…”
Section: Relationship Statussupporting
confidence: 66%
“…Carpenter, 2012;DeSteno, Bartlett, Braverman, & Salovey, 2002;Harris, 2003aHarris, , 2005Kato, 2014aKato, , 2014b and alternative interpretations that can account for gender differences in infidelity responses (for review, see Edlund & Sagarin, 2017;Kato, 2017); for example, social cognitive theory (Harris, 2003a(Harris, , 2003b and the double-shot hypothesis (DeSteno & Salovey, 1996;Harris, 2003a). The imagination hypothesis on jealousy (Kato, 2014a(Kato, , 2014b proposes that gender differences in responses to infidelity are derived from the capacity for imagination which varies between genders, particularly men's explicit sexual imagery and women's explicit romantic imagery. According to the imagination hypothesis, men and women should not differ in response to a partner's sexual and emotional infidelity provided that men and women can imagine emotional and sexual infidelity vividly and realistically.…”
Section: Imagination Hypothesismentioning
confidence: 99%
See 3 more Smart Citations